Glyoxalase 1 overexpression does not affect atherosclerotic lesion size and severity in ApoE−/− mice with or without diabetes. (18th August 2014) - Hanssen, Nordin M.J.; Brouwers, Olaf; Gijbels, Marion J.; Wouters, Kristiaan; Wijnands, Erwin; Cleutjens, Jack P.M.; De Mey, Jo G.; Miyata, Toshio; Biessen, Erik A.; Stehouwer, Coen D.A.; Schalkwijk, Casper G.
Abstract: Aims: Advanced glycation end-products (AGEs) and their precursors have been associated with the development of atherosclerosis. We recently discovered that glyoxalase 1 (GLO1), the major detoxifying enzyme for AGE precursors, is decreased in ruptured human plaques, and that levels of AGEs are higher in rupture-prone plaques. We here investigated whether overexpression of human GLO1 in ApoE −/− mice could reduce the development of atherosclerosis. Methods and results: We crossed C57BL/6 ApoE −/− mice with C57BL/6 GLO1 overexpressing mice (huGLO1 +/− ) to generate ApoE −/− ( n = 16) and ApoE −/− huGLO1 +/− ( n = 20) mice. To induce diabetes, we injected a subset with streptozotocin (STZ) to generate diabetic ApoE −/− ( n = 8) and ApoE −/− huGLO1 +/− ( n = 13) mice. All mice were fed chow and sacrificed at 25 weeks of age. The GLO1 activity was three-fold increased in huGLO1 +/− aorta, but aortic root lesion size and phenotype did not differ between mice with and without huGLO1 +/− overexpression. We detected no differences in gene expression in aortic arches, in AGE levels and cytokines, in circulating cells, and endothelial function between ApoE −/− mice with and without huGLO1 +/− overexpression. Although diabetic mice showed decreased GLO1 expression ( P < 0.05) and increased lesion size ( P < 0.05) in comparison with non-diabetic mice, GLO1 overexpression also did not affect the aortic root lesion size or inflammation in diabetic mice. Conclusion: In ApoE −/− mice with or without diabetes, GLO1 overexpression did not lead to decreased atherosclerotic lesion size or systemic inflammation. Increasing GLO1 levels does not seem to be an effective strategy to reduce glycation in atherosclerotic lesions, likely due to increased AGE formation through GLO1-independent mechanisms.